The role of ERP systems in enhancing the productive potential of enterprises in the sectoral economy (Economics and region, 2025)
This work focuses on detailed examination of how integrated corporate resource planning platforms influence productivity growth across companies from various sectors amid digitalization processes. Functional capabilities of contemporary technological solutions have been identified within context of unifying core business processes and rational utilization of corporate capabilities. Five key directions of influence on human, material, financial, organizational and informational assets have been distinguished. Significance of such platforms as catalysts for digitalization processes and instruments for achieving operational excellence has been substantiated. Organizational and methodological aspects of implementation have been analyzed, considering key success conditions, management of organizational transformations and need for adaptation to specific sector characteristics. It has been proven that effectiveness of technological solutions is determined by comprehensive approach to unifying technical, organizational and managerial components while accounting for peculiarities of individual economic branches. Paper examines how integrated platforms transform resource management through process automation, real-time data synchronization and advanced analytical instruments. Special emphasis is placed on sectoral adaptation mechanisms, demonstrating how manufacturing, agricultural and service sectors require distinct platform configuration approaches. Based on systematic analysis of recent international research, study proves that platform effectiveness is determined by comprehensive approach to integrating technological, organizational and managerial components considering specific features of particular economic sector. Practical cases from leading companies demonstrate measurable improvements in operational performance including twenty to fifty percent time savings, fifteen percent inventory reduction and enhanced customer satisfaction levels. Research contributes to understanding integrated planning platforms not merely as software solutions but as strategic instruments for comprehensive business transformation enabling enterprises to achieve sustainable competitive advantages through enhanced productivity, improved decision-making capabilities and optimized resource allocation. Findings emphasize importance of systematic approach to platform implementation combining technical infrastructure, organizational readiness, continuous improvement practices and strong leadership support. Future development directions include integration with machine learning technologies, distributed device networks and distributed ledger technology opening new opportunities for manufacturing productivity enhancement and supply chain optimization.